High-Intensity Exercise May Compromise Renal Morphology in Rats - Aparicio, V. A.; Tassi, M.; Nebot, E.; Camiletti-Moirón, D.; Ortega, E.; Porres, J. M.; Aranda, P. (International Journal of Sports Medicine, 2014)
We investigated the renal effects of a high-intensity exercise (HIE) program based on strength training. 20 Wistar rats were randomly assigned to 2 experimental groups performing HIE or control over 12 weeks. Urinary volume, pH, citrate and calcium, and plasma urea, total proteins, creatinine, albumin, lactate dehydrogenase, creatine kinase (CK), calcium, magnesium, corticosterone and testosterone were measured. We also studied renal morphology with the Fibrosis HR® software. Plasma urea and CK concentrations were higher in the HIE compared to the control group (p<0.05), whereas plasma creatinine was lower (p<0.01). Plasma corticosterone was higher (p<0.05) and testosterone lower (p<0.01) in the HIE group. Except for the higher urinary volume found in the HIE group (p<0.05), no differences between groups were observed in the rest of urinary parameters analyzed. Renal interstitial connective tissue was ~30% higher in the HIE group (p<0.05). Glomerular tufts and mesangial areas were also higher in the HIE group (all, p<0.05). No differences between groups were observed in the glomerular area. Overall, HIE promoted a worse morphological renal profile that might be associated with a higher risk for incidence of kidney disease in the long-term. The stress induced by the type of exercise performed could be on the basis of this worse morphological renal status.
Keywords: strength training; plasma; urine; kidney; renal morphology; rat